Squamous cell carcinoma arising in a mature cystic teratoma of the ovary with synchronous invasive lobular breast cancer: case report. - Filippakis, G M; Lagoudianakis, E E; Genetzakis, M; Antonakis, P; Papadima, A; Boussiotou, A; Katergiannakis, V; Manouras, A (Eur J Gynaecol Oncol, 2006)
Malignant transformation of a mature ovarian cystic teratoma is the most serious complication of this relatively common neoplastic lesion. While any constituent tissue of the teratoma can undergo malignant transformation, squamous cell carcinoma represents approximately 80% of those malignancies. Furthermore, the synchronous occurrence of a second malignancy in that setting is extremely rare. Preoperative diagnosis of malignant transformation within a mature cystic teratoma is extremely difficult and poses a great challenge to current clinical surgical practice. The particularly aggressive behavior of this rare tumor, also poses significant surgical managing dilemmas. We present a case report of a premenopausal woman with an invasive squamous cell carcinoma arising in a mature cystic teratoma and a synchronous invasive lobular carcinoma of the breast.
Keywords: Adult; Breast Neoplasms; Carcinoma, Lobular; Carcinoma, Squamous Cell; Female; Humans; Neoplasm Staging; Neoplasms, Multiple Primary; Ovarian Neoplasms; Teratoma